Learning Bribri and Learning in Bribri: A Pedagogical Proposal to Using an Indigenous Language - Zúñiga-Morales, Alex; Carvajal-Jiménez, Vivian (Revista Electrónica Educare, 2022)
Objective. To present the results of a pedagogical proposal for using the Bribri language with second-grade students at Las Brisas School, Cabagra (Zúñiga Morales, 2019), Costa Rica. Methodology. Two innovative works were developed: adapting an instrument to determine the linguistic skills in the Bribri language of the participating population; in addition, a pedagogical proposal was designed to be applied over three consecutive weeks in all subjects of the school curriculum (except the Spanish course). Results. With this proposal, not only the linguistic competencies in the Bribri language were improved, but all the curricular contents that the Ministry of Public Education (MEP) established for second grade in different subjects were facilitated. The students went from a Basic Beginner Level to a Medium Intermediate Level and were able to develop small presentations, incorporate idiomatic expressions into their daily life classroom and create with language. Conclusion. The indigenous language should not only be studied from isolated vocabularies and abstract grammar. It is necessary to use it in all kinds of everyday situations and force its constant use with various idioms and tools that allow its users to create with language progressively. It is proven that conditions can be facilitated to contribute valuable elements to the linguistic revitalization of the school classroom. It is stated that not only is the indigenous language learned, but also that various disciplinary knowledge can be accessed through it.